Effect of Hydrolysate Derived from Subcritical Seawater Treatment of Buckwheat Waste on the Growth of Lettuce (Lactuca sativa L.) - Yongheng Yuan; Faqinwei Li; Naoto Shimizu (Plants)
This study explores the effects of a subcritical seawater treatment (SST) on buckwheat waste (BW), and the use of the hydrolysate as a liquid fertilizer to improve the growth of lettuce (Lactuca sativa L.). Three temperature treatments (110 °C, 170 °C, 230 °C) were used for the SST, and the ionic composition in the seawater achieved the depolymerization and degradation of BW. The X-ray diffraction of the residual solids showed that the structure of BW was destroyed. Compared with seawater, the hydrolysate contained higher amounts of elements beneficial to plant growth, such as N, P, K, and organic compounds such as phenolics and sugars, as a result of the degradation of BW caused by the SST. The hydrolysate was tested as a liquid fertilizer (treatments H110°C, H170°C, H230°C) to irrigate lettuce. The content of proteins, phenolics, and chlorophyll, as well as the weight of the lettuce in the H110°C and H170°C treatments, were significantly higher than those in the seawater and the H230°C irrigation treatments (p < 0.05). The hydrolysate from the SST of BW, being rich in various organic and inorganic nutrients, can act as a liquid fertilizer that promotes the growth of lettuce, whereas hydrolysate from higher SST temperatures might inhibit the growth of lettuce, because of the excessive total nitrogen and organic acid.